MECHANICAL PROPERTIES AND ETHYLENE GAS ABSORPTION EFFICIENCY OF COMPOSITE PAPER FROM CORN HUSK FIBERS WITH RECYCLED POLYETHYLENE TEREPHTHALATE - Dangrattanawong, Thaweephum; wiprachot, Nantiya; Silpawilawan, Wanthana (Srinakharinwirot University Journal of Sciences and Technology, 2024)
The objectives of this study were to study the properties of composite sheets made from corn husk fibers combined with r-PET fibers and the efficiency of ethylene absorption of composite sheets mixed with activated carbon powder. Firstly, the raw fibers were treated with 0.1, 0.15, 0.20 and 0.25% (W/V) sodium hydroxide solution. It was found that the concentration of 0.25% (W/V) was most suitable for fiber treatment. The composite sheets were formed by using the mulberry paper making techniques, standard size 110 g/m2 according to the kraft paper product of Thai industrial standard (TIS. 170-2550), which various ratio of corn husk fibers and r-PET fibers of 90:10, 80:20, 70:30 and 60:40. The ratio of 90:10 sample exhibited great physical and mechanical properties, average percentage humidity 3.64%, average water absorption time was 13.51 seconds, average bursting strength 110.03 kPa and tensile strength 2.02 kN/m. Then activated carbon powder were added in the best composite sheet (90:10) at 0%, 5% and 10%. The results shown that the composite sheets containing 10% activated carbon powder could be the best absorber and better than pure activated carbon powder because of Kaew Khamin mangoes had the lowest percentage of weight loss at 22.57% and 20.07%, respectively.